Pengaruh Pemberian Pupuk Limbah Cair Tahu Terhadap Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max L. Merril) - Juis Fitra; Bustari Badal; Dewirman Prima Putra (Jurnal Research Ilmu Pertanian, 2022)
Research on the effect of giving tofu liquid waste fertilizer on the growth and yield of soybean (Glycine max L. Merril), has been carried out in Koto Panjang Ikur Koto Village, Koto Tengah District, Padang City. Starting from April to July 2019. The study aims to get the best concentration of tofu liquid waste fertilizer for the growth and yield of soybean (Glycine max L. Merril) The experiment used a Randomized Block Design (RBD) with 5 and 5 groups of treatment, so there were 25 experimental units. The treatments given in the experiment were various concentrations of tofu liquid waste fertilizer as follows: A: 0 ml/liter water/plot, B: 30 ml/liter water/plot, C: 60 ml/liter water/plot, D: 90 ml/liter water/plot, E : 120 ml/liter water/plot. The results showed no effect significantly different on the number of primary branches, flowering age, harvest age, weight of 100 seeds, but significantly different on plant height, percentage of pithy pods per plant, dry seed weight per plant and dry seed weight per plot, but the yield was still below description. From the results of this study, it is recommended to increase the concentration of tofu liquid waste fertilizer by more than 120 ml/liter of water/plot against the observation parameters to get results that match the description